PENGEMBANGAN INSTRUMEN ASESMEN TES HIGHER ORDER THINKING SKILLS PADA PEMBELAJARAN IPAS KELAS V SD - Yuliyani, Dewi; Supriyadi; Yeri Sutopo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop an assessment instrument to measure the high-level thinking abilities (HOTS) of fifth grade elementary school students in science learning. The instrument developed consists of 10 descriptive questions that have been validated. Data analysis using the Aiken formula and Rasch model shows that the instrument has good quality in measuring HOTS. In both small and large scale tests, the instrument was proven to be unidimensional and reliable. However, further analysis revealed the existence of several items that indicated gender bias. However, overall the instrument can be used to measure student HOTS. The results of this research contribute to the development of better assessment instruments to measure elementary school students' higher-order thinking abilities. Keywords: test assessment, HOTS, IPAS, rasch